Mulheres profissionais bem-sucedidas: Um estudo exploratório no contexto organizacional brasileiro. - Mancini, Monica (2005)
The globalization of the economy and the fast technological changes occurred in the last twenty years are changing the society as a whole, and they are being reflected in several segments: economical, political, social, cultural, among others. In this new world order, the women come assuming an important role. They are transposing organizational barriers and taking executive positions in the companies that, formerly, were inaccessible. This thesis has as objective to study the characteristics of the successful women's personality, to identify the factors that contributed to its professional success and the barriers that hinder or obstruct its ascension in the organizations. The research was performed in a sample of 227 successful women of the organizational brazilian context, divided in 3 groups: 56 academics, 54 entrepreneurs and 117 executives. The data collection was performed through questionnaires and interviews. The results exposed that in regard to personality characteristics, those women evidence a high degree of self-efficacy, high need for achievement and internal locus of control to deal with organizational barriers and to reach its objectives. The factors that contributed to professional success women were: internal motivation to overcome the obstacles, participative and group leadership style, work opportunity, investment in education, support of the family, advisory process as psychological support and leader's model as personal reference. On the other hand, this research reveals that the organizational culture was the stronger barrier that the researched women confronted to ascend to positions more elevated in the organizations. This study exposes for the need of a cultural change in regarding to feminine work in the organizations, giving it the same conditions of equality and opportunity of professional growth in relation to the men. Through this study, we hope to have contributed to give to the organizations managers a perception more based on this subject. With that, it should be waited that the organizations find new ways to live together with gender differences, respecting and creating different politics that benefit as much the man as the woman.